IMPLEMENTATION OF PROJECT-BASED LEARNING THROUGH STEM APPROACH TO IMPROVE STUDENTS' SCIENCE PROCESS SKILLS AND LEARNING OUTCOMES - Helvy Aprianty; Abdul Gani; Andi Ulfa Tenri Pada (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2020)
This study aimed to determine PjBL-STEM implementations effect to improve science process skills and students’ learning outcomes on the material of substances and their characteristics. The type of research used was a quasі-experiment with a pre-test post-test control group design. The research subjects were students of class VII Darul Ihsan Islamic Junior High School Aceh Besar, which consisted of eight classes. The sample group was determined by purposive sampling technique so that two classes were obtained as the research sample, namely class VII-G as an experimental class and VII-H as a control class. The results showed that the implementation of the PjBL-STEM model could increase students’ science process skills. The average students’ science process skills in the control and experimental classes were 53 and 55 with sufficient categories. However, after implementing the Discovery Learning model in the control class and PjBL-STEM in the experimental class, the students' science process skills' average score increased to 76 with good categories and 86 with excellent categories. The PjBL-STEM model was also able to improve students’ learning outcomes. Based on the results of the t-test analysis with a significant score of 0.05, it showed that the post-test scores in both classes were obtained t-count (2.011) > t-table (1.666), so it was concluded that there was a significant difference between the two classes. N-gain testing showed an increase in students’ learning outcomes between the control and experimental classes with scores of 74 and 79. This study concluded that the PjBL-STEM model could improve science process skills and students’ learning outcomes.